Effects of blade lean angle on a hydraulic retarder. (5th May 2016) - Chen, Ming; Guo, Xuexun; Tan, Gangfeng; Pei, Xiaofei; Zhang, Wei
The rotor and stator blade lean angle of a hydraulic retarder is one of its main geometrical design parameters. The objective of this study is to clarify the effects of blade lean angle on hydraulic retarder performance. In this article, we employ a computational fluid dynamic approach to numerically investigate the fluid flow of a hydraulic retarder for rotor blade lean angles of 35°, 40°, 43°, and 45° in the direction of rotation, where the stator employs an equivalent angle, and all other geometries are held constant. The numerical results of the braking torque were validated against available experimental results. Analyses of torque performance, flow field, and energy loss are conducted in this study. Additionally, the outer loop oil flow rate is used as another indicator of hydraulic retarder heat exchange performance. The results indicate that with increasing blade lean angle, both the braking torque and oil volume flow rate first increase and then decrease, reflecting an optimal value. The lean angle affects secondary vortex flows and separate flows. Relatively large lean angles may enhance the occurrence of separate flow, whereas relatively small lean angles may cause in the oil inlet region. An optimal blade lean angle achieves a smooth oriented inner flow and a maximum braking torque.